Environmental influences on the LIGO gravitational wave detectors during the 6th science run. (14th January 2015) - Effler, A; Schofield, R M S; Frolov, V V; González, G; Kawabe, K; Smith, J R; Birch, J; McCarthy, R
Abstract: We describe the influence of environmental noise on Laser Interferometric Gravitational-Wave Observatory (LIGO) detectors in the sixth science run, from July 2009 to October 2010. We show results from experimental investigations testing the coupling level and mechanisms for acoustic, electromagnetic/magnetic and seismic noise to the instruments. We argue the sensors' importance for vetoes of false positive detections, report estimates of the noise sources' contributions to the detector background, and discuss the ways in which environmental coupling should be reduced in the LIGO upgrade, Advanced LIGO.